Linda L. Layne: Home and Homeland. The Dialogics of Tribal and National Identities in Jordan. - Braae, Christel (Tidsskriftet Antropologi, 1998)
The Dialogics of Tribal and National Identities in Jordan. Anmeldes af Christel Braae